Case study for Pelorus Intelligence and Technology Academy Sdn.Bhd. the impacts of internship abroad program towards students in Netherlands Maritime Institute of Technology (NMIT) / Siti Nooraini Sahak - Sahak, Siti Nooraini (2011)
This study is to analyze the importance of the internship program to the students’ especially in maritime field in Malaysia and to see whether the company can give benefit or weaknesses to them in order to increase expertise in maritime field in Malaysia. This also will look at the certain issue and it focus how the impact of internship abroad program towards students in Netherlands Maritime Institute of Technology and the challenges face by them in perfective social adaptation, communication and technology at the host country. This case study will identify the elements or factor, then the researcher will select the major factor for each element and conduct case study to support each other.